Circadian circuits in humans: White matter microstructure predicts daytime sleepiness. (January 2020) - Koller, Kristin; Rafal, Robert D.; Mullins, Paul G.
Abstract: The suprachiasmatic nucleus of the hypothalamus is the chief circadian pacemaker in the brain, and is entrained to day-night cycles by visual afferents from melanopsin containing retinal ganglion cells via the inferior accessory optic tract. Tracer studies have demonstrated efferents from the suprachiasmatic nucleus projecting to the paraventricular nucleus of the hypothalamus, which in turn project to first-order sympathetic neurons in the intermedio-lateral grey of the spinal cord. Sympathetic projections to the pineal gland trigger the secretion of the sleep inducing hormone melatonin. The current study reports the first demonstration of potential sympathopetal hypothalamic projections involved in circadian regulation in humans with in vivo virtual white matter dissections using probabilistic diffusion tensor imaging (DTI) tractography. Additionally, our data shows a correlation between individual differences in white matter microstructure (measured with fractional anisotropy) and increased daytime sleepiness [measured with the Epworth Sleepiness Scale (ESS, Johns, 1991)]. Sympathopetal connections with the hypothalamus were virtually dissected using designated masks on the optic chiasm, which served as an anatomical landmark for retinal fibres projecting to the suprachiasmatic nucleus, and a waypoint mask on the lateral medulla, where hypothalamic projections to the sympathetic nervous system traverse in humans. Sympathopetal projections were demonstrated in each hemisphere in twenty-six subjects. The tract passed through the suprachiasmatic nucleus of the hypothalamus and its trajectory corresponds to the dorsal longitudinal fasciculus traversing the periaqueductal region and the lateral medulla. White matter microstructure (FA) in the left hemisphere correlated with high scores on the ESS, suggesting an association between circadian pathway white matter microstructure, and increased daytime sleepiness.